The Influence of AI-Powered Chatbots on Reducing Mental Health Care Barriers in Rural Areas - Asim, Muhammad; Hoor Fatima Yousaf; Usama Nasir; Muhammad Abubakar Farooq; Faraya Yousaf, (Dialogue Social Science Review (DSSR), 2025)
Lack of staff, stigma, financial barriers, and remote locations often impede access to mental health services in rural areas. A potential remedy to these barriers is AI-powered chatbots, which provide scalable, affordable, and accessible mental health support. This study examines how AI-powered chatbots can improve access to rural mental health services and outcomes. AI chatbots fill gaps in mental health services that may be lacking in traditional care. Providing personalized service, reducing stigma, and providing 24-hour support, rural participants said they felt more buy-in to using AI chatbots to access mental health services and visits. Convenience and privacy are the key factors they consider. Additionally, because chatbots are accessible and scalable. Therefore, it is an effective alternative to traditional medicine. This is especially true in areas where there is no mental health infrastructure. However, the research also focuses on ethical issues. It also entails human care, which ensures effective treatment. And two dice. Resulting in better mental health in the rural areas.